Problem continuity in discontinuity of development of Serbian industry - Šljukić Marica (Sociološki Pregled, 2017)
In this paper the author uses a comparative analysis in order to show the discontinuity in the process of the industrial development of the Serbian society, as well as to point out the fact that the almost same problems have not been mastered throughout the whole process of industrialization. Besides the historical data, the data of the empirical research are used. The goal of the empirical research was to determine the real and the possible degree and intensity of the influence of the structural social changes to the organizing of industrial work. The research had been done from 2011 to 2013 using the multiple case study method, and it included six organizations from different sectors of industry. By comparison of different phases of the industrial development in Serbia the author concludes the continuity of the following problems: accumulation of capital, technical and technological underdevelopment and dependence, raw materials dependence, and the deficit of the competent work force (especially managers). The biggest and the basic problem, which encompasses all four problems mentioned above, has been the absence of the strategy of the industrial development throughout the whole process of this development.